RAS in the Central Nervous System: Potential Role in Neuropsychiatric Disorders - Rocha, Natalia P.; Simoes e Silva, Ana Cristina; Prestes, Thiago R. R.; Feracin, Victor; Machado, Caroline Amaral; Ferreira, Rodrigo Novaes; Teixeira, Antonio Lucio; de Miranda, Aline Silva (Current Medicinal Chemistry, 2018)
Background: The Renin-Angiotensin System (RAS) is a key regulator of cardiovascular and renal homeostasis, but also plays important roles in mediating physiological functions in the central nervous system (CNS). The effects of the RAS were classically described as mediated by angiotensin (Ang) II via angiotensin type 1 (AT1) receptors. However, another arm of the RAS formed by the angiotensin converting enzyme 2 (ACE2), Ang-(1-7) and the Mas receptor has been a matter of investigation due to its important physiological roles, usually counterbalancing the classical effects exerted by Ang II. Objective: We aim to provide an overview of effects elicited by the RAS, especially Ang-(1-7), in the brain. We also aim to discuss the therapeutic potential for neuropsychiatric disorders for the modulation of RAS. Method: We carried out an extensive literature search in PubMed central. Results: Within the brain, Ang-(1-7) contributes to the regulation of blood pressure by acting at regions that control cardiovascular functions. In contrast with Ang II, Ang-(1-7) improves baroreflex sensitivity and plays an inhibitory role in hypothalamic noradrenergic neurotransmission. Ang-(1-7) not only exerts effects related to blood pressure regulation, but also acts as a neuroprotective component of the RAS, for instance, by reducing cerebral infarct size, inflammation, oxidative stress and neuronal apoptosis. Conclusion: Pre-clinical evidence supports a relevant role for ACE2/Ang-(1-7)/Mas receptor axis in several neuropsychiatric conditions, including stress-related and mood disorders, cerebrovascular ischemic and hemorrhagic lesions and neurodegenerative diseases. However, very few data are available regarding the ACE2/Ang-(1-7)/Mas receptor axis in human CNS.
Keywords: mas receptor